Pengaruh Pemberian Suplemen Vitamin B12 Sebagai Neuroregenerasi Pada Pasien Tinnitus: Literature Review - Mohammad Ihza Satriatama; Sulistyani Sulistyani; Nining Lestari; Yan Wirayudha (Universitas Muhammadiyah Purwokerto, 2022)
Background: Tinnitus is one of the most common complaints in family medicine practice, with the incidence of tinnitus being highly variable and dominated by subjective tinnitus rather than objective tinnitus, about 30-40% of the adult population has experienced tinnitus in their lifetime, and 0.5-2.5% of the population has impaired quality of life. Because the research conducted is still controversial, this study is a study to look specifically at the effect of giving vitamin B12 on the treatment of tinnitus and so it is important to do further research to prove the administration of vitamin B12 supplements as neuroregeneration in tinnitus patients. In the discussion later, the researcher divides the research subjects into two parts, namely humans and animals. Human subjects to see the effect of vitamin B12 in the healing process of tinnitus and animal subjects to see the effect of vitamin B12 in neuroregeneration. This is expected to provide a reference in the treatment of tinnitus in Indonesia. Objective: :To see specifically the effect of giving vitamin B12 in the neuroregeneration process in tinnitus patients. Methods: This research method is a literature review study. Data collection techniques through Pubmed and Science direct have been limited for the last 10 years. The article review was carried out on 292 scientific articles and obtained 7 articles that met the restriction criteria and the PICO. Results: The results of a review of 7 articles found that Vitamin B12 can regenerate the myelin sheath (3 articles) and Vitamin B12 can reduce noise or improve tinnitus (4 articles). Conclusion: There is potential of Vitamin B12 on the healing process through neuroregeneration of cells in tinnitus patients. Vitamin B12 has the potential to prevent disease or reduce severity in tinnitus patients. Latar Belakang: Tinnitus merupakan salah satu keluhan yang banyak ditemukan dalam praktik kedokteran keluarga dengan angka kejadian tinnitus sangat bervariasi dan didominasi oleh tinnitus subjektif daripada tinnitus objektif, sekitar 30-40% pada populasi dewasa dan sebesar 0,5-2,5% terganggu kualitas hidupnya. Penelitian tentang pengaruh dari pemberian vitamin B12 terhadap pengobatan tinnitus masih cukup beragam hasilnya, sehingga penting dilakukan penelitian lebih lanjut untuk membuktikan pemberian suplemen vitamin B12 sebagai neuroregenerasi pada pasien tinnitus. Pembahasan dalam penelitian ini peneliti perlu membedakan subjek penelitian menjadi dua bagian yaitu pada manusia dan hewan. Subjek manusia untuk melihat efek vitamin B12 dalam proses penyembuhan tinnitus dan subjek hewan untuk melihat efek vitamin B12 dalam neuroregenerasi. Hal ini diharapkan dapat memberikan referensi dalam pengobatan tinnitus di Indonesia. Tujuan: untuk mengetahui pengaruh pemberian vitamin B12 dalam proses neuroregenerasi pada pasien tinnitus. Metode penelitian ini adalah studi literatur review. Teknik pengambilan data melalui Pubmed dan Science direct limitasi 10 tahun terakhir. Telaah artikel dilakukan pada 292 artikel ilmiah dan didapatkan 7 artikel yangsesuai kriteria restriksi dan PICO. Hasil telaah didapatkan 7 artikel dengan hasil bahwa Vitamin B12 dapat meregenerasi selubung myelin (3 artikel) dan Vitamin B12 dapat menurunkan kebisingan atau mangalami perbaikan tinnitusnya (4 artikel). Kesimpulan: Terdapat pengaruh Vitamin B12 terhadap proses penyembuhan melalui neuroregenerasi sel pada pasien tinnitus. Literatur juga menyebutkan bahwa Vitamin B12 berpotensi mencegah penyakit atau menurunkankeparahan pada pasien tinnitus.